A multicenter, single‐arm, open‐label, phase 2 study of apitolisib (GDC‐0980) for the treatment of recurrent or persistent endometrial carcinoma (MAGGIE study). Issue 22 (7th September 2016) - Makker, Vicky; Recio, Fernando O.; Ma, Ling; Matulonis, Ursula A.; Lauchle, Jennifer O.; Parmar, Hema; Gilbert, Houston N.; Ware, Joseph A.; Zhu, Rui; Lu, Shan; Huw, Ling‐Yuh; Wang, Yulei; et al.
Abstract : BACKGROUND: The current single‐arm, open‐label trial was designed to evaluate the activity of apitolisib (GDC‐0980), a dual phosphoinositide 3‐kinase/mammalian target of rapamycin (PI3K/mTOR) inhibitor, in patients with advanced endometrial cancer (EC). METHODS: Patients with recurrent or persistent EC who were treated with 1 to 2 prior lines of chemotherapy but no prior PI3K/mTOR inhibitor received oral apitolisib at a dose of 40 mg daily during 28‐day cycles until disease progression or intolerable toxicity occurred. Patients with type I/II diabetes who required insulin were excluded. The primary endpoints were progression‐free survival (PFS) at 6 months and objective response rate. RESULTS: A total of 56 women were enrolled, including 13 (23%) with well‐controlled diabetes. Reasons for discontinuation were disease progression (24 patients; 43%), adverse events (13 patients; 23%), and withdrawal by subject (12 patients; 21%). Grade 3/4 apitolisib‐related adverse events were hyperglycemia (46%), rash (30%), colitis (5%), and pneumonitis (4%) (toxicities were graded according to the National Cancer Institute Common Terminology Criteria for Adverse Events [version 4.0]). The PFS rate at 6 months was 20% (Kaplan‐Meier estimate; 95% confidence interval [95% CI], 7%‐33%). The objective response rate was 6% (confirmed). The median PFS was 3.5 months (95% CI, 2.7‐3.7 months) and the median overall survival was 15.7 months (95% CI, 9.2‐17.0 months). Nineteen patients discontinued the study before the first tumor assessment. Dose reductions were required for 4 diabetic (31%) and 18 nondiabetic (42%) patients. Comprehensive molecular profiling of 46 evaluable archival tumor samples demonstrated that 57% of patients had at least 1 alteration in phosphatidylinositol‐4, 5‐bisphosphate 3‐kinase catalytic subunit alpha ( PIK3CA ), phosphatase and tensin homolog ( PTEN ), or AKT1 . All 3 patients with a confirmed response had at least 1 alteration in a PI3K pathway gene. CONCLUSIONS: The antitumor activity noted with the use of a dose of 40 mg of apitolisib daily was limited by tolerability, especially in diabetic patients. Patients with PI3K pathway mutations may have derived enhanced benefit from apitolisib. Cancer 2016;122:3519–28 . © 2016 American Cancer Society . Abstract : Patients with endometrial cancer with ≥1 alteration in phosphoinositide 3‐kinase (PI3K) signaling components may potentially benefit from a single‐agent dual PI3K/mammalian target of rapamycin (mTOR) inhibitor, apitolisib, if sufficient drug exposure is received. Apitolisib has a relatively narrow therapeutic index, with poor tolerability and limited efficacy. Selective inhibitors of PI3K/mTOR signaling may benefit from patient enrichment via biomarker data. See also pages 3428–9.